Travel satisfaction revisited. On the pivotal role of travel satisfaction in conceptualising a travel behaviour process. (December 2017) - De Vos, Jonas; Witlox, Frank
Abstract: Over the past years a substantial amount of studies has indicated that travel satisfaction is affected by a wide range of elements such as trip duration, travel mode choice and travel-related attitudes. However, what is less explored is that this travel satisfaction is not only an outcome of travel-related preferences and choices, but that travel satisfaction can also be a predictor of travel-related components. In this conceptual paper we tend to fill the gaps in the existing − albeit rather fragmented − literature concerning travel satisfaction. We provide an overview of the elements explaining travel satisfaction, and possible outcomes of travel satisfaction, with a focus on (i) subjective well-being, (ii) travel mode choice, (iii) travel-related attitudes, and (iv) the residential location. Furthermore, we suggest a continuous cyclical process including the four above mentioned elements in which travel satisfaction plays an essential role; a process which can result in the formation of travel habits.